Analysis Abnormal Return Eid Al-Fitr on Food and Beverages Company Listed In Indonesia Stock Exchange Year 2013 – 2017 - Ranny Rizky Ananda (Journal of Economics, Business, and Government Challenges, 2019)
Efficient market is a price that reflects all the information available, the more efficient the market is very difficult for investors to obtain abnormal return. Abnormal return can happen the event of holiday effectEid Al-Fitr. The purpose of this study was to examine the differences of abnormal returns before and after Eid Al-Fitr and to examine the effect of one week before Eid Al-Fitr and one week after Eid Al-Fitr against abnormal return in Food and Beverages sub sector. the observation period is one week or seven days Eid Al-Fitr and one week or seven days after Eid Al-Fitr for five years (2013-2017). The results of hypothesis testing in this study used the analysis of different test paired t-test sample with SPSS program and 5% significance level (0.05) and by using Multiple Regression Analysis with Eviews program. The sampling technique in this research is purposive sampling to get the sample of 11 companies. The result of the test is obtained (1) there is difference of abnormal return before and after Eid Al-Fitr, (2) the week Eid Al-Fitr has significant effect to abnormal return, (3) a week after Eid Al-Fitr does not affect abnormal return.